#
Give the slope-intercept form and standard form of the following

1. m=-6, b=3

2. (2,-3), b=1

3. (2,-3) and (0,1)

2
by Waterlily

Log in to add a comment

1. m=-6, b=3

2. (2,-3), b=1

3. (2,-3) and (0,1)

by Waterlily

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Slope Y-intercept Form

1. y = -6x + 3

2. y = -2x + 1

3. y = -2x + 1

Standard Form

1. 6x + y = 3

2. 2x + y = 1

3. 2x + y = 1

~hope it help :)

1. y = -6x + 3

2. y = -2x + 1

3. y = -2x + 1

Standard Form

1. 6x + y = 3

2. 2x + y = 1

3. 2x + y = 1

~hope it help :)

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Slope Intercept Form ----- y = mx + b

Standard Form ----- ax + by = c

__1. m = -6, b = 3__

SIF: y = mx + b

** **__y = -6x + 3__ (just substitute)

SF: y = -6x + 3

*transpose variables to the other side such that it'll have the format of sf*

__6x + y = 3__

__2. (2, -3) ; b = 1__

SIF: y = mx + b

-3 = 2m + 1

-4 = 2m

---- -----

2 2

**m = -2 ---- **Now we have m then substitute so the answer is

__y = -2x + 1.__

SF: y = -2x + 1

__2x + y = 1__

__3. (2, -3) and (0, 1)__

SIF: (solve for m)

** **change in y

m = -----------------

change in x

1 + 3

= --------

0 - 2

4

= ---------- or -2 so therefore,**m = -2**

- 2

y = mx + b

1 = -2(0) + b SIF:__ ____y = -2x + 1__

1 = b

**b = 1**

SF: y = -2x + 1

** **__2x + y = 1__

--

--**Good night***--*

Standard Form ----- ax + by = c

SIF: y = mx + b

SF: y = -6x + 3

-3 = 2m + 1

-4 = 2m

---- -----

2 2

change in x

1 + 3

= --------

0 - 2

4

= ---------- or -2 so therefore,

- 2

y = mx + b

1 = -2(0) + b SIF:

1 = b

SF: y = -2x + 1

--

--